DASYMETRIC MODELLING OF POPULATION DISTRIBUTION – LARGE DATA APPROACH - Dmowska, Anna (Quaestiones Geographicae, 2019)
Existing resources of population data, provided by national censuses in the form of areal aggregates, have usually insufficient resolution for many practical applications. Dasymetric modelling has been a standard technique to disaggregate census aggregates into finer grids. Although dasymetric modelling of population distribution is well-established, most literature focuses on proposing new variants of the technique, while only few are devoted to developing broad-scale population grids that could be used for real-life applications. This paper reviews literature on construction of broad-scale population grids using dasymetric modelling. It also describes an R implementation of fully automated framework to calculate such grids from aggregated data provided by national censuses. The presented implementation has been used to produce high resolution, multi-year comparable, U.S.-wide population datasets that are the part of the SocScape (Social Landscape) project.